Racial and ethnic differences in fatal child abuse and neglect and the intersection of community poverty: U.S., 2003 to 2022 - Rebecca F. Wilson; Xin Yue; Karen E. Thomas; Krishna Kiran Kota; Carter J. Betz (Child Protection and Practice)
Introduction: In the U.S., child abuse and neglect (CAN) is a significant public health problem. Poverty is a well-known correlate of CAN. Objective: Examine racial and ethnic differences in fatal CAN among U.S. children and the intersection of community poverty. Participants and methods: This study integrated National Violent Death Reporting System (NVDRS) data, county poverty data, and population estimates data. We used NVDRS data to examine fatal CAN for children aged 0–17 years for 2003–2022. Fatal CAN was defined as a homicide precipitated by abuse or neglect by a parent or caregiver. Racial and ethnic differences in fatal CAN were examined using pairwise comparisons. Community poverty quartiles for fatal CAN cases were determined using county-level poverty data and population estimate data for 2003–2022. Results: During 2003–2022, NVDRS captured 6182 fatal CAN cases; 57.3% were boys; 79.6% were aged 0–5 years. An argument (21.4%), child's history of abuse (20.1%), and intimate partner violence (IPV; 15.6%) were the three most common precipitators of fatal CAN. IPV as a precipitator was most common among Asian or Pacific Islander (API; 33.0%), Hispanic (16.4%), and White (19.1%) victims than Black victims (10.8%; p < 0.05). More than one in ten (13.9%) fatal CAN deaths co-occurred with the perpetrator's suicide; this occurred most commonly among API victims (38.1%; p < 0.05) than Black (5.8%), multiracial (13.4%), and White (13.9%) victims. A larger proportion of fatal CAN among API victims (14.2%; p < 0.05) was precipitated by a crisis than did fatal CAN of Black (3.3%), multiracial (4.7%), and White (4.5%) victims.During 2003–2022, more than one in three (35.9%) fatal CAN victims resided in communities classified as the most impoverished; 52.7% of AI/AN victims resided in these communities, followed by Black (46.7%), Hispanic (31.3%), multiracial (30.9%), White (28.7%), and API (12.4%) victims. During this same period, 47.8% of API fatal CAN victims resided in communities with the least poverty, followed by White (17.3%), Hispanic (15.3%), multiracial (16.6%), and Black (10.1%) victims. Conclusions: Fatal CAN is preventable. Employing multiple strategies, at various levels (e.g., individual, familial, community), might aid in preventing nonfatal and fatal CAN.